1993
DOI: 10.1515/hfsg.1993.47.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Radical Activity Associated with the Growth of White-Rot Fungi

Abstract: A sensitive and selective chemiluminescence method has been used to detect hydroxyl radicals during the growth of white-rot fungi. The investigation reveals that fungal growth is accompanied by a generation of hydroxyl radicals which in turn are considered to be responsible for the initial phase of fungal-mediated wood degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 26 publications
(14 reference statements)
0
46
0
Order By: Relevance
“…Although the participation of hydroxyl radicals was long ago postulated in P. chrysosporium (Forney et al, 1982;Kutsuki & Gold, 1982;Bes et al, 1983;Kirk & Nakatsubo, 1983;Faison & Kirk, 1983;Evans et al, 1984), subsequent studies have shown that the attack of lignin model compounds by Fenton chemistry leads to products different from those detected in ligninolytic cultures or by isolated peroxidases (Kirk et al, 1985). Nevertheless, there is evidence that supports a role for Fenton chemistry in the degradation of lignocellulose by P. chrysosporium (Kremer & Wood, 1992a, b;Backa et al, 1993;Wood, 1994;Henriksson et al, 1995;Tanaka et al, 1999). It has been shown that cellobiose dehydrogenase (CDH), an oxidative enzyme secreted by both brown-and white-rot fungi, is capable of generating hydroxyl radicals by reducing Fe(III) and producing H 2 O 2 (Kremer & Wood, 1992a, b;Henriksson et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Although the participation of hydroxyl radicals was long ago postulated in P. chrysosporium (Forney et al, 1982;Kutsuki & Gold, 1982;Bes et al, 1983;Kirk & Nakatsubo, 1983;Faison & Kirk, 1983;Evans et al, 1984), subsequent studies have shown that the attack of lignin model compounds by Fenton chemistry leads to products different from those detected in ligninolytic cultures or by isolated peroxidases (Kirk et al, 1985). Nevertheless, there is evidence that supports a role for Fenton chemistry in the degradation of lignocellulose by P. chrysosporium (Kremer & Wood, 1992a, b;Backa et al, 1993;Wood, 1994;Henriksson et al, 1995;Tanaka et al, 1999). It has been shown that cellobiose dehydrogenase (CDH), an oxidative enzyme secreted by both brown-and white-rot fungi, is capable of generating hydroxyl radicals by reducing Fe(III) and producing H 2 O 2 (Kremer & Wood, 1992a, b;Henriksson et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Further support for this hypothesis is that white rot fungi, which do not utilize the hydroxyl radical as the major oxidant (30,32), also produce oxalate (39,40,42,49). Despite reports on how the hydroxyl radical may be formed in white rot fungi (4,17,18), it is unlikely that oxalate would have a role in its formation. The chemical signatures of wood affected by white rot fungi and brown rot fungi are different (30).…”
Section: Discussionmentioning
confidence: 99%
“…The quinone undergoes cyclic oxidation-reduction reactions, serving as a shuttle for electrons from intracellular donors to extracellular acceptors. Although a similar mechanism has been proposed for white rot fungi (4,17,18) for hydroxyl radical formation, product analysis suggests that hydroxyl radical oxidation is relatively minor in comparison to peroxidase oxidation (30,32). The role of oxalate, ubiquitously found in brown rot fungi, as a chelating agent, and the role of pH, which is altered by the fungus, are not clear.…”
mentioning
confidence: 90%
“…Besides their role in extending the kind and number of lignin units that can be oxidized by the action of laccase, natural mediators are important because ligninolytic enzymes have to act indirectly during the early phases of plant cell wall degradation due to size exclusion limitations (13,14). Other small molecular agents participating in lignin degradation and produced directly or indirectly by ligninolytic enzymes include manganic ion (Mn 3ϩ ) (24,27,50), the cationic radical of the fungal metabolite veratryl (3,4-dimethoxybenzyl) alcohol (26), and activated oxygen species such as the hydroxyl radical (HO ⅐ ) and superoxide anion radical (O 2 ⅐Ϫ ) (2,15,27). Except for O 2 ⅐Ϫ , all of these compounds are able to oxidize lignin units.…”
mentioning
confidence: 99%